Tumour-infiltrating cytotoxic T lymphocytes in somatotroph pituitary neuroendocrine tumours - Iacovazzo, Donato; Chiloiro, Sabrina; Carlsen, Eivind; Bianchi, Antonio; Giampietro, Antonella; Tartaglione, Tommaso; Bima, Chiara; Bracaccia, Maria Elena; Lugli, Francesca; Lauretti, Liverana; Anile, Carmelo; Gessi, Marco; et al. (Endocrine, 2020)
Introduction Somatotroph pituitary tumours are often resistant to first-generation somatostatin analogues and can invade the surrounding structures, limiting the chances of curative surgery. Recent studies suggested that the immune microenvironment and pro-angiogenic factors can influence neuroendocrine tumour prognosis. In this study, we aimed to investigate the prognostic role of immune cell-specific markers and endocan, a proteoglycan involved in neoangiogenesis and cell adhesion, in a cohort of acromegaly patients who underwent pituitary surgery as first-line treatment. Subjects and methods Sixty four eligible subjects were identified. CD4+, CD8+ and CD68+ cells and endocan expression were evaluated by immunohistochemistry and results correlated with clinical and neuroradiological findings. Responsiveness to somatostatin analogues was assessed in patients with persistent disease following surgery. Results The number of CD8+ lymphocytes was significantly lower in tumours with cavernous sinus invasion (median 0.2/HPF, IQR: 2.2) compared with those without cavernous sinus invasion (median 2.4/HPF, IQR: 2.3; P = 0.04). Tumours resistant to first-generation somatostatin analogues had lower CD8+ lymphocytes (median 1/HPF, IQR: 2.4) compared with responders (median 2.4/HPF, IQR: 2.9; P = 0.005). CD4+ lymphocytes were observed sporadically. The number of CD68+ macrophages and the endothelial or tumour cell endocan expression did not differ based on tumour size, cavernous sinus invasion or treatment responsiveness. Conclusions Our study suggests that a lower number of CD8+ lymphocytes is associated with cavernous sinus invasion and resistance to treatment with first-generation somatostatin analogues in acromegaly patients. These results highlight a potential role of the tumour immune microenvironment in determining the prognosis of somatotroph pituitary tumours.